Exact black hole formation in asymptotically (A)dS and flat spacetimes - Xuefeng Zhang; H. Lü (Physics Letters B, 2014)
We consider four-dimensional Einstein gravity minimally coupled to a dilaton scalar field with a supergravity-inspired scalar potential. We obtain an exact time-dependent spherically symmetric solution describing gravitational collapse to a static scalar-hairy black hole. The solution can be asymptotically AdS, flat or dS depending on the value of the cosmological constant parameter Λ in the potential. As the advanced time u increases, the metric approaches the static limit in an exponential fashion, i.e., e−u/u0 with u0∼1/(α4M0)1/3, where M0 is the mass of the final black hole and α is the second parameter in the potential. Similarly to the Vaidya solution, at u=0, the spacetime can be matched to an (A)dS or flat vacuum except that at the origin a naked singularity may occur. Moreover, a limiting case of our solution with α=0 gives rise to an (A)dS generalization of the Roberts solution. Our results provide a new model for investigating formation of real life black holes with Λ≥0. For Λ<0, it can be instead used to study non-equilibrium thermalization of certain strongly-coupled field theory.